PERANCANGAN DESAIN GRAFIS MEDIA PROMOSI WEBSITE PASAR PAPRINGAN BAGI KELUARGA URBAN DI INDONESIA - Steven Arden; R.A Dita Saraswati; Puspita Yuli Pradita (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2019)
Papringan Market is located in Ngadiprono Hamlet, Ngadimulyo Village, Kedu District, Temanggung, and Central Java. The Papringan market has a big idea to build a village from the village by revitalizing it. The Papringan market has good potential for tourist areas, because it has a unique transaction method, this market uses